1992
DOI: 10.1093/carcin/13.7.1289
|View full text |Cite
|
Sign up to set email alerts
|

Phenol sensitization of DNA to subsequent oxidative damage in 8-hydroxyguanine assays

Abstract: The DNA base adduct, 8-hydroxyguanine (8-OHGua), has been reported to be a key biomarker relevant to carcinogenesis and cellular oxidative stress important in tumor promotion. Although investigators often report artificially high levels of 8-OHGua in DNA samples that have been exposed to phenol solutions and/or air during processing, few quantitative results are available. We show that routine phenol-based DNA purification procedures can increase 8-hydroxydeoxyguanosine (8-OHdG) levels 20-fold in samples that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 0 publications
1
42
1
Order By: Relevance
“…[12][13][14][15] The former induces strand breaks and the latter oxidizes DNA. It was reported that DNA recovered from a gel visualized by EtBr plus light was a poor substrate for in vitro transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] The former induces strand breaks and the latter oxidizes DNA. It was reported that DNA recovered from a gel visualized by EtBr plus light was a poor substrate for in vitro transcription.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that light irradiation in the presence of ethidium bromide (EtBr), organic solvent extractions, and UV-irradiation damage DNA, [12][13][14][15][16] and that the formation of DNA lesions results in transcriptional inhibition and errors. [17][18][19][20] Thus, we purified closed circular molecules and linearized DNAs in the same gel to compare the effect of the topology precisely.…”
Section: Experimental Schemementioning
confidence: 99%
“…[23][24][25] Phenol and atmospheric oxygen are proposed to be responsible for the artificial formation of 8-oxodG during these procedures. In this study, incubation with enzymes during the isolation and hydrolysis of DNA was performed under an argon atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Because LC/MS/MS and LC/MS do not require sample derivatization for assay, the oxidation of DNA is suppressed [34]. On the other hand, in the case of HPLC/ECD, a significant amount of oxidative damage can be induced during the isolation of DNA, especially in the presence of phenol [40] . Phenol, a reducing agent, is thought to reduce metal ions (e. g., iron ions) present in biological extracts .…”
Section: Measurement Of Oxidative Damage To Dnamentioning
confidence: 99%